ANALISIS SENTIMEN APLIKASI JASA KURIR DI PLAY STORE MENGGUNAKAN ALGORITMA NAIVE BAYES - Adhitia Erfina; Muhamad Fani Al-shufi (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
Along with the passage of sales through the marketplace. The courier service industry has also experienced an increase. There are many choices of courier services to choose from, each courier service has different qualities depending on how the service provided by the courier service to customers. To find out the quality of courier services, this research was carried out, this research was conducted on courier service applications on Playstore, usually the best application predicate is for applications with a high number of downloads and ratings, while comments from users must also be considered to get results which is relevant. In this study, the Naïve Bayes algorithm is used because it has a high level of accuracy to determine the best courier service application. Based on the research that has been done, the highest accuracy value is obtained by the JNT application of 100% but has a positive sentiment of 50 reviews. The two JNE applications with an accuracy value of 98% with a positive sentiment of 46 reviews, the three ninjaxpres applications with an accuracy value of 97.87% with a positive sentiment of 49 reviews, the fourth by the Sicepat application with an accuracy value of 97.85% with a positive sentiment of 47 reviews and finally by the Idexpress application with an accuracy value of 94% with a positive sentiment of 49 reviews.